Effect of low-dose versus higher-dose antenatal iron supplementation on child health outcomes at 36 months of age in Viet Nam: longitudinal follow-up of a cluster randomised controlled trial. Issue 3 (22nd September 2017) - Hanieh, Sarah; Ha, Tran T; Simpson, Julie A; Braat, Sabine; Thuy, Tran T; Tran, Thach D; King, Janet; Tuan, Tran; Fisher, Jane; Biggs, Beverley-Ann
Abstract : Introduction: Intermittent iron-folic acid supplementation (IFA) is currently recommended for pregnant women in populations where anaemia prevalence among pregnant women is <20% or if daily iron is not acceptable. The effect of providing lower doses of antenatal elemental iron through intermittent regimes on longer-term health outcomes in childhood is unclear. Methods: A prospective cohort study conducted between May 2012 and May 2014 in Viet Nam among children of 36 months of age, born to women previously enrolled in a cluster randomised controlled trial of antenatal micronutrient supplementation (daily IFA (60 mg elemental iron) vs twice-weekly IFA (60 mg elemental iron) vs twice-weekly multiple micronutrient (MMN) supplementation (60 mg elemental iron)). Primary outcomes were height-for-age z-scores (HAZ), according to WHO growth standards and cognitive composite scores (Bayley Scales of Infant and Toddler Development, third edition) at 36 months of age. Results: A total of 1017 children born to mothers enrolled in the cluster randomised trial were assessed at 36 months of age. Adjusted mean differences (MDs) in HAZ were –0.14 (95% CI –0.28 to –0.01) and –0.15 (95% CI –0.29 to –0.01) in children born to mothers who received twice-weekly IFA or MMN compared with those who received daily IFA. Children born to mothers who received twice-weekly MMN had lower composite motor scores compared with those who received daily IFA (MD –2.07, 95% CI –4.11 to –0.03). There were no differences in composite cognitive scores in the twice-weekly compared with daily regimens. Conclusions: Low-dose antenatal IFA supplementation (120 mg elemental iron per week) resulted in lower HAZ and motor composite scores in children compared with higher-dose antenatal IFA supplementation (420 mg elemental iron per week). This highlights the importance of adequate iron stores during pregnancy and the need for careful monitoring when lower-dose antenatal iron regimens are used. Trial registration number: Australia New Zealand Clinical Trials Registry: 12610000944033.